Evaluation Of Programs For Stunting Prevention Management At Tajinan Public Health Center - rifzul maulina (Universitas Nahdlatul Ulama Surabaya, 2021)
Stunting is one of the problems that can human development globally. East Java is one of the provinces that has a high prevalence of stunting. This shows the low quality of health services. The government is committed to reduce stunting rates through several health policies. The policy is in the form of a program launched by the Indonesian Ministry of Health (Kemenkes), namely the Healthy Indonesia Program with a Family Approach (PIS-PK), Provision of Supplementary Food and the First 1000 Days of Life (HPK). The purpose of this study was to evaluate the intervention program for the management of nutritional status of stunting under five with elements of input, process and output. This research is a qualitative research. The initial informants were determined by purposive sampling technique. The data collection method was through in-depth interviews, observation and documentation of 6 initial informants consisting of the head of the puskesmas, the coordinating midwife for Children and Mother Health, the nutrition coordinator, the village midwife, framework and some target mothers. Two triangulation informants consisting of the family health coordinator and the district health office nutrition coordinator. The results showed that at the input stage, the health workers involved still needed additional, there were no nutrition workers. In the process element, some of the programs were well implemented including the family approach through home visits by framework, healthy programs for pregnant women, exclusive breastfeeding, growth monitoring, supplementary feeding, giving vitamin A except for the taburia program. In the output element, the coverage of the prevalence of stunting in the Tajinan Public Health Center, Malang Regency in 2018 was 17.24%